An Investigation of The Application of Communicative Language Teaching in a Speaking Class at MAN Lubuk Alung - Rahmawati, Sari (FKIP - Universitas Riau, 2020)
This research was a case study research that aimed to investigate the application of Communicative Language Teaching (CLT) in a speaking class at MAN Lubuk Alung. The subject of the study was a certified High School English teacher in Lubuk Alung who has 25 years teaching experience. The teacher’s speaking class was observed whether or not matched with the principles of CLT. The data were analyzed through some steps of qualitative data analysis, they are data managing, reading, describing, classifying, and interpreting. The result of the research revealed that the process of teaching speaking were not appropriate with CLT principles. Conversely, she seemed still to apply the characteristics of conventional teaching method.